Studi Eksperimental Penambahan Biji Plastik dan Fly Ash Pada Karakteristik Campuran Aspal (AC-WC) - Yulianti, Dimitri; Ulfah, Luthfiyyah; Lubis, Lega Reskita; Haki, Helmi (Jurnal Talenta Sipil, 2025)
Infrastructure development requires innovative approaches to enhance the performance of pavements while supporting environmental sustainability. This study aims to identify the impact of adding LDPE 812 plastic pellets and fly ash on the characteristics of an asphalt mixture in the AC-WC layer using the wet mix method. The tests were conducted with variations in the plastic pellet content of 0%, 6%, 6.5%, and 7%. The additives used were LDPE 812 plastic pellets with a specific gravity of 0.917 g/cm³ and fly ash with a specific gravity of 2.71 g/cm³. The tests included aggregate analysis, asphalt characteristics, and Marshall testing to evaluate stability, flow, voids in mix (VIM), voids in mineral aggregate (VMA), voids filled with asphalt (VFA), and Marshall Quotient (MQ). The results of the study showed that adding plastic pellets improved the stability of the asphalt mixture, especially at a plastic pellet content of 6%. At the 6% plastic pellet and 5% asphalt content, the stability value reached 3092 kg, indicating a significant improvement in resistance to deformation and flow. The flow value for the mixture with 6% plastic pellets at 5% asphalt content reached an average of 4.32 mm, while with 7% plastic pellets at the same asphalt content it reached 3.37 mm. At an asphalt content of 5%, the MQ value for a normal asphalt mixture is 338 kg/mm, while an asphalt mixture with 6% plastic pellets reaches 780.51 kg/mm, but decreases to 311.81 kg/mm at a plastic pellet content of 7%. This study suggests that asphalt mixtures with the addition of plastic pellets and fly ash can be an effective and environmentally friendly alternative for the development of sustainable road pavements.